Pro krimìnal′no-reguvantne dezìnformuvannâ âk zasìb protidїї zločinnìj dìâl′nostì - Kogutič, Ivan (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The author analyses separate aspects of disputable in modern criminalistics question: admissibility of using in judicature disinformation class fictions. The conclusion about expediency of using tactical techniques and combinations based on hidden information to obtain the desired and caused by tasks of justice results is grounded.
Keywords: Ukraina; środki przeciwdziałania przestępczości; dezinformacja; karno-relewantna dezinformacja